2017
DOI: 10.1371/journal.pone.0183681
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of endometrial mesenchymal marker SUSD2 causes cell senescence and cell death in endometrial carcinoma cells

Abstract: The cause of death among the majority of endometrial cancer patients involves migration of cancer cells within the peritoneal cavity and subsequent implantation of cancer spheroids into neighbouring organs. It is, thereby, important to identify factors that mediate metastasis. Cell adhesion and migration are modified by the mesenchymal stem cell (MSC) marker Sushi domain containing 2 (SUSD2), a type I transmembrane protein that participates in the orchestration of cell adhesion and migration through interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…For example, opening of chromatin at and upstream of the SUSD2 promoter corresponded to increased abundance of SUSD2 + eMSC in A83-01 cultures. Interestingly, SUSD2 has been shown to prevent senescence and cell death in tumor cells ( Zhang et al, 2017 ), suggesting its induction is important for expansion of cultured eMSC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, opening of chromatin at and upstream of the SUSD2 promoter corresponded to increased abundance of SUSD2 + eMSC in A83-01 cultures. Interestingly, SUSD2 has been shown to prevent senescence and cell death in tumor cells ( Zhang et al, 2017 ), suggesting its induction is important for expansion of cultured eMSC.…”
Section: Discussionmentioning
confidence: 99%
“…The present study presents the first evidence, to our knowledge, that SUSD2 acts as an oncogene in GC. 20 We show here that inhibiting SUSD2 mRNA expression using a specific siRNA inhibits cell proliferation, invasion, and migration, indicating that SUSD2 is required to establish the malignant phenotype of GC cells. To address this issue in more detail, we performed PCR array analysis and found that FZD7, CDH2, TGFB1, SPARC, ITGA5, and ZWB1 mRNAs were overexpressed in concert with SUSD2.…”
Section: Discussionmentioning
confidence: 69%
“…SUSD2 is expressed in endometrial carcinoma cells, and suppressing its expression following treatment with TGFβ or a specific siRNA increases apoptosis and senescence. The present study presents the first evidence, to our knowledge, that SUSD2 acts as an oncogene in GC …”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of SUSD2 is associated with increased tumor invasion and decreased survival in a mouse model [ 36 ]. Silencing of SUSD2 expression in endometrial carcinoma cells results in cell death [ 37 ]. Thus, it has been suggested that reducing expression of this protein might be a therapeutically useful strategy.…”
Section: Resultsmentioning
confidence: 99%